The Implementation of Drilling Technique to Help Students’ Speaking Skill - saputra, iqbal latif (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2023)
The teachers’ teaching technique is very important in the learning process, especially for speaking skills. The aim of this study is to describe how teacher implemented the teaching speaking skill by using the Drilling Technique in the eighth grade of SMPIT Logaritma Karanganyar and the teacher’s and students’ perspectives on the use of drilling technique. This study used a qualitative method.  The subjects of this research are an English teacher and the eighth-grade students. Interviews and observations were conducted to obtain research data. The data analysis technique used is data reduction, data analysis, and drawing conclusions. Based on the findings from the implementation of the drilling technique, the teacher applied four steps in teaching speaking using the drilling technique. The steps applied by the teacher is in accordance with the theory described by Freeman. According to the observations and interviews data, the researcher found out that the students and teacher did not find any difficulties in the process of learning speaking using the drilling technique.